Advances in 3D printing technology for preparing bone tissue engineering scaffolds from biodegradable materials - Wang, Zhen; Sun, Yanan; Li, Chen (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Bone tissue engineering (BTE) provides an effective repair solution by implanting osteoblasts or stem cells into biocompatible and biodegradable scaffolds to promote bone regeneration. In recent years, the rapid development of 3D bioprinting has enabled its extensive application in fabricating BTE scaffolds. Based on three-dimensional computer models and specialized “bio-inks,” this technology offers new pathways for customizing BTE scaffolds. This study reviews the current status and future prospects of scaffold materials for BTE in 3D bioprinting. Methods This literature review collected recent studies on BTE and 3D bioprinting, analyzing the advantages and limitations of various scaffold materials for 3D printing, including bioceramics, metals, natural polymers, and synthetic polymers. Key characteristics like biocompatibility, mechanical properties, and degradation rates of these materials were systematically compared. Results The study highlights the diverse performances of materials used in BTE scaffolds. Bioceramics exhibit excellent biocompatibility but suffer from brittleness; metals offer high strength but may induce chronic inflammation; natural polymers are biocompatible yet have poor mechanical properties, while synthetic polymers offer strong tunability but may produce acidic by-products during degradation. Additionally, integrating 3D bioprinting with composite materials could enhance scaffold biocompatibility and mechanical properties, presenting viable solutions to current challenges. Discussion This review summarizes recent advances in 3D bioprinting for BTE scaffold applications, exploring the strengths and limitations of various materials and proposing composite material combinations to improve scaffold performance. By optimizing material selection and combinations, 3D bioprinting shows promise for creating customized scaffolds, offering a new technical route for clinical applications of BTE. This research provides a unique perspective and theoretical support for advancing 3D bioprinting technology in bone regeneration, outlining future directions for BTE materials and 3D bioprinting technology development.